Food Safety Practices of Household Food Preparers in Akwa Ibom State, Nigeria. - Udoh, Ekaette; Udoh, Edet (Advances in Social Sciences Research Journal, 2020)
Generally, study analysed the food safety practices of household food preparers in Akwa Ibom state. A multi-stage sampling procedure was used to collect cross-sectional data from 457 respondents. Specifically, study determined the prevalence, margin and intensity of and factors influencing food safety practices of household food preparers. Given two critical indices 0.62 and 0.42, the study showed that the prevalence of best food safety practices is 49.45% and 97.8% respectively. Results of the disaggregated mean prevalence show that households that carry out less than best food safety practices do so sometimes and not often respectively while those who carry out best practices, do so most times. The mean margins, based on the two respective critical indices 0.62 and 0.42, suggest that, minimally, policy could seek to raise the value of the food safety and dietary practices index of households with less than best practices by 0.08 and 0.04 respectively. The values of the intensity (of the mean margin)0.009, 0.002 and 0.004, 0.0003 , in pairs each representative of the two critical indices-0.62 and 0.42, show that the deviation is more severe when the mean is adopted as critical index both when only deviating and all households are considered. Results of the fractional probit regression indicated that education, household income and confidence in safety labels are statistically significant in explaining the probability of households carrying out food safety practices. The gap between households who carry out less than best and best food safety practices should be bridged.